Using Line x Tester Analysis for Earliness and Plant Height Traits in Sunflower (Helianthus annuus L.) - Muhammad Saeed, Shah Masaud Khan, Bashir Ahmad, Sher Asalm Khan, Habib Ahmad, Ayub Khan (Recent Research in Science and Technology, 2009)
Line x tester analysis, involving four lines and four testers were made in sunflower for four parameters. The variance due to GCA and SCA showed that gene action was predominantly additive for days to first flowering (DFF), days to hundred percent flowering (DH%F) and plant height (PH), whereas predominance of non-additive genetic effect was discovered for days to maturity (DM). Both additive and non-additive genetic interaction was important for morpho-physiological characters in sunflower. The line TS-18 was the best general combiner for characters like DFF and PH, whereas line TS-17 was the best general combiner for DH%F and DM. The tester R-25 proved to be the best general combiner for DFF, DH%F and DM, whereas the tester 291RGI proved to be the best general combiner for PH. The SCA estimates were highest in cross TS-335 x TR-9 for DFF, TS-18 x R-25 for DH%F and DM. For PH, the best SCA cross was TS-18 x 291RGI. The best GCA parents as TS-17, TS-18, R-25 and 291RGI are recommended, which may be exploited for varietal improvement in different cross combination especially in synthetic production, whereas the three best SCA crosses are recommended Ã‚Â to be the best hybrids for cultivation and be included in the national uniformity yield trial for its exploration in multilocation. Additive type of gene action was observed for DFF, DH%F and PH. These characters may further be improved through simple selection method in early generation, whereas non-additive type of gene action was observed for DM, which is desirable for heterosis breeding and may be exploited in hybrid seed production.